Sufi Islam and the nation state: Darul Arkam movement in the post Suharto era of Indonesia - Ahmad Ubaedillah (Indonesian Journal of Islam and Muslim Societies, 2015)
Modernity as a global phenomenon has been the most driving matter, saidthose scholars of modernity, that potentially threat the existent of traditionand religion. Both would vanish once the project of secularism accomplishes.However, since the global modernity, whether represented by secular state,nation state, and democracy, failed to fulfil its promises, tradition and religionsin general have reemerged to be likely a new device employed by theiradherents to express their grievances and discontents. In such regard, recentIslamic movements promoting the slogan of “back to the authentic Islam”can be a better example to examine the relationship between modernity andreligion. Accordingly, the paper, based on my field research, would discussthe role of religion in modern era as represented by Darul Arkam, an Islamicspiritual maternity or Tarekat (Thar6iqa, Arabic) in Indonesia after the collapseof Suharto’s military regime in 1998. Originally, the movement of DarulArkam came into being in Malaysia as a spiritually-social-urban Muslim organization.How did its leaders understand Islam in regard to changing socialand political situation and how did they combine economic and religiousactivities will be the main topics of the paper, together with their views oncontemporary issues related to Islam and politics after Soeharto era.Modernitas sebagai sebuah fenomena global merupakan faktor palingberpengaruh, demikian para teoritis moderisme menyatakan, terhadapkeberadaan tradisi dan agama. Kedua unsur ini akan lenyap seiring dengandengan keberhasilan yang dicapai oleh proyek sekularisme yang berlangsungsecara global. Namun demikian, sejak gerakan modernisme, yang diwakili antaralain oleh konsep negara sekuler, negara bangsa, dan demokrasi, dianggap telahgagal memenuhi janji-janjinya, tradisi dan agama secara umum kembali menjadimedia untuk mengungkapkan kekecewaan mereka terhadap kegagalan danakibat-akibat yang ditimbulkan oleh modernism. Pada situasi ketidak puasaanini, gereakan-gerakan Islam dewasa ini yang mempropagandakan gagasan“kembali kepada Islam yang otentik” dapat menjadi sebuah contoh yang tepatuntuk menganalisa hubungan kekinian anatara modernitas dan agama.Berdasarkan riset lapangan, tulisan ini akan memaparkan peran koumintasagama, yang diwakili oleh organisasi Darul Arkam, sebuah perkumpulan yangdiikat oleh rasa persaudaran Muslim atau biasa dikenal dengan tarekat, di Indonesiapaska jatuhnya kekuasaan Presidean Soeharto pada 1998. Darul Arkamsendiri merupakan organisasi komunitas Muslim urban yang muncul pertamakali di Malaysia. Bagaimana pemimpin Darul Arkam memahami ajaran Islamdalam situasi sosial-politik yang tengah berubah di Indonesia dan bagaimanamereka menggabungkan antara aktifitas keagamaan dan ekonomi akan menjadipembahasan pokok tulisan ini, selain respon mereka terhadap isu-isu yangberkembang di era reformasi.